The conflictological profile of the organisation as an element of cultural identity - N. I. Pryanikova (Вестник университета)
In contemporary research on organisational effectiveness, the concept of culture is gaining ground. Not only organisational and/or national culture is considered, but also the whole range of local subcultures: professional, personal, age, etc., which also need to be analysed and taken into account. This circumstance affects the micro- and macro-level functioning of the organisation in the cultural code. The article studies the phenomenology of conflict from the perspective of an organisation’s conflictological profile, which is a reflection of its cultural identity. A typological cross-section of the conflict, its operational, strategic and symbolic types has been revealed. They have individual characteristics and have an impact on the functioning of the organisation, shaping its unique conflictological profile.